If it's not what You are looking for type in the equation solver your own equation and let us solve it.
16/13-t=5/13
We move all terms to the left:
16/13-t-(5/13)=0
We add all the numbers together, and all the variables
-t+16/13-(+5/13)=0
We add all the numbers together, and all the variables
-1t+16/13-(+5/13)=0
We get rid of parentheses
-1t+16/13-5/13=0
We multiply all the terms by the denominator
-1t*13+16-5=0
We add all the numbers together, and all the variables
-1t*13+11=0
Wy multiply elements
-13t+11=0
We move all terms containing t to the left, all other terms to the right
-13t=-11
t=-11/-13
t=11/13
| 5(r+4)=40 | | -24=-2k+6 | | -26-2r=36 | | m/16-9=-3 | | 1.75x+6.3=16.45 | | 4x-2x(-3)x=20 | | (3x+30)+(2x-10)=4x+40 | | 2x^2+10x+20=-10x-4 | | 7x-36=x+9 | | 11x–6x=6 | | 4x=2(2x-6) | | 7x-36=5x-1 | | y=-4-24 | | 20-0,5w=0 | | x(x+3)-6=x^2+5x-8 | | 1/20=13/x= | | 6a–4=8 | | 12x-4=4x+31 | | 1.75x=1.15 | | 2.40x=50.4 | | 15-2b=21 | | (3x-13)+(x-3)=80 | | 5x+6=4x+31 | | 20f=10f-200 | | -4(b+3)+-10=-10 | | –15=x–7 | | 5h−–17=52 | | 10+w/4=11 | | 8x+4-(6+6x)=14 | | -4x=-512 | | (5−x)^(1/2)−2x=0. | | x÷2.40=50.4 |